The effects of rhizobial herbs on in vitro rumen fermentation profiles in cattle - Razlan, Shakirah (2016)
Rhizobial herb such as turmeric (Curcuma longa), ginger (Zingiber officinale), galangal (Alpinia galangal ) and Javanese ginger (Curcuma zanthorrhiza) have a lot of health beneficial used not only for human, but also for animal, and those rhizobial herbs were selected in this research. The objectives of this research was to study the effect of feeding different type of rhizobial herbs on in vitro rumen fermentation of cattle. The method that has been used for this reseach is by using in vitro rumen fermentation, where the environmental condition of the rumen is created like the real rumen environment, including the temperature and anaerobic condition.The gas production produced during fermentation was measured for every 2 hours for 24 hours.These rhizobial herbs were mixed as a supplement of the basal diet (control diet) which were rice straw and concentrate. The comparison is done between rhizobial herbs and control diet. The in vitro dry matter digestibility and fermentation profiles that includes pH, total gas production, volatile fatty acids (VFA) and concentration of ammonia were analysed. Proximate analysis were done to determine the chemical composition of the samples used in this study. The dry matter (DM), ash, crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF) and acid detergent lignin (ADL) were evaluated. There are 3 replicates for each treatment and the experiment is run for two times. The data collected was then analyzed using Statistical Analysis Software (SAS). For the gas production, the results shows that there were no significant difference (P>0.05) of the total production of gas in all different types of rhizobial herbs when compare with the control diet. The same result of no significant differences also goes to In Vitro Dry Matter Digestibility (IVDMD). There is also no significant differences (P>0.05) were observed for the rumen pH among rhizobial herbs and control diet. For the main volatile fatty acids produced in rumen, only acetic acid in turmeric have significant differences (P<0.05) with control diet, meanwhile other rhizobial shows no significant differences. The propionic and butyric acid in all treatment with control diet also shows no significant difference (P>0.05). Also, ammonia concentration shows there were no significant differences (P>0.05). Lastly, significant difference (P<0.05) were observed on nutritive values between samples and control diet for the DM, OM, CP, ADF, ADL and NDF content. Based on these results, it shows that there are only significance difference among rhizobial herbs and control diet for volatile fatty acid which is acetic acid in turmeric, and nutritive value of feed sample but no significance difference in terms of gas production, ammonia concentration, pH, rate of digestion, IVDMD, propionic acid and butyric acid. Futher study can be done by difffers the percentage on supplementation rhizobial herbs in the feed that may give effect on the digestibility as a recommendation. Microbial population parameter was suggested to be added in the future study as microbial population also a major contribution to ruminal fermentation.